An aftertaste of Cartesian salad? Pre-reflective self-consciousness, Peirce, and the study of cognition in the wild. (April 2023) - Steiner, Pierre
I situate the originality and the ambiguities of the target paper in the context of post-cognitivist cognitive science and in relation with some aspects of Charles Sanders Peirce's anti-Cartesianism. I then focus on what the authors call « pre-reflective self-consciousness », highlighting some ambiguities of the characterizations they propose of this variety of consciousness. These ambiguities can become difficulties once one grants a crucial methodological role to this consciousness in the study of cognitive activities.